Implementation of Visual Auditory Kinesthetic Learning Model in Mastering Arabic Vocabulary at MTsN 5 Pandeglang: Implementasi Model Pembelajaran Visual Auditory Kinestetik dalam Penguasaan Mufradāt di MTsN 5 Pandeglang - Hani’atul Mabruroh; Siti Nurfadlilah; Ahmad Hidayatullah Zarkasyi; Nia Hayati Nufus (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
This paper discusses the importance of education as a conscious and planned effort to create an effective learning environment, enabling students to develop their spiritual, intellectual, and linguistic potential. One of the challenges in learning foreign languages, particularly Arabic, lies in mastering vocabulary. The research focuses on implementing the Visual, Auditory, and Kinesthetic (VAK) learning model to address this issue, which integrates visual, auditory, and physical engagement in the learning process at State Junior High School 5 Pandeglang Banten. Researchers use quantitative-experimental research, Pre-Experimental with a Pretest-Posttest Group Design approach, and researchers use the Probability Sampling method. Using random sampling techniques, researchers chose a sample size of 20% from 200 students. The methods used to collect data are tests and documentation. The data analysis method in this study used the non-parametric Mann-Whitney t-test with the help of SPSS 25. The U or Mann-Whitney value is 0.000, and the Wilcoxon W value is 2296.00. The Z value is -6.709 with a significant Asymtop value of 0.000. Because the considerable value is less than 0.005 (0.000<0.005), Ha is accepted, and Ho is rejected. So, it can be concluded that using the VAK Learning Model influences the mastery of Arabic vocabulary at MTs Negeri 5 Pandeglang, Banten. With the results of this research, the researcher decided to make the following suggestion for all teachers to develop student learning efficiency, especially in mastering Arabic vocabulary with good models. Hopefully, this research will become a reference for future researchers, completing deficiencies and expanding knowledge. Keywords: Arabic Learning, Learning Model, Visual Auditory and Kinesthetic, Vocabulary Mastery